الضمانات التأديبية لمقاضي في التشريع الج ا زئري - شايب محمد; صح ا روي زكرياء (University of Eloued جامعة الوادي, 2020)
يعد القاضي العنصر الأساسي و الرجل الأول في المحاكم، وهو بدوره يسعى جاهدا لتحقيق العدالة، ومع ذلك قد يرتكب القاضي خطأ مهنيا يمس شرف المهنة، لذا منح للقاضي ضمانات تأديبية عند وقفه وعند سير الدعوی. يعد المجلس الأعلى للقضاء هيئة ادارية قضائية متخصصة، في رقابة إنضباط القضاة وتأديبهم، ومهام أخرى متعلقة بالقضاة. ولهذا وضع المشرع الجزائري القانون العضوي 04 /11المتضمن القانون الأساسي للقضاء والقانون العضوي 04 /12 المتعلق بتشكيلة المجلس الأعلى للقضاة وسير عمله. The judge is the main element and the first man in the courts, and he, in turn, strives to achieve justice. However, the judge may make a professional mistake that affects the honor of the profession, so he granted the judge disciplinary guarantees when he stopped and when the case proceeded. The Supreme Judicial Council is a specialized judicial administrative body, to monitor the discipline and discipline of judges, and other tasks related to judges. That is why the Algerian legislator put the organic law 11/4, which includes the basic law for the judiciary and the organic law 12/12 related to the composition and functioning of the Supreme Council of Judges.
مدكرة ماستر
Keywords: القاضي.المجلس .المشروع; Juge, Conseil, Projet